(3OjhGf GHf gGfF GdCfOdSjs - (3GHf gGfjA GdCfOdSj , eMeO Hf gGfjA Hf eMeO Hf SYOhf GdCROj GdCfOdSj, CHh GdbGSe,J (B362 (3g` s ((3eMeO Hf eMeO GdgQjOj GdMdHj s)
(3ChdgG (B:s
(3jhe YQjV aj GdaNGQ Whjd eG JfbVj ZQQ dg hMLhd s
(3BNQgG (B:s
(3JQGK jMji Yf CH hLO ef HYO eG bWY Cda ZeO LQOg Hjf jOj eYO bO jfUQ Gdehdi HSja GdYHO s
(3fSNI SGOSIs
(3haj ChdgG Jedjc HJGQjN (B1080(3g```` hYOI JedjcGJ hoeWGdYGJs
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B130 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B12 - (3U (B88s
Keywords: (3GdCOHs